Assessment of Community Participation in Heritage Management in Algeria: Case of Safeguarded Sectors (Analysis Through Legislation Documents) - Sabiha Timhadjelt; Soumia Bouzaher; Sarra Kachef (Richtmann Publishing, 2023)
Heritage management in Algeria is a process governed by legal texts that date from the end of the 20th century. In the light of the international issues at stake in community-based management, it appears essential that heritage management in Algeria should be directed to participatory approaches with a vision of socio-cultural development and sustainability. This paper aims to investigate and assess community participation in the legislation regulating heritage management, specifically safeguarded areas and their permanent plans for safeguarding and enhancing safeguarded areas (PPSMVSS).To achieve this, a documentary research was carried out on several laws and executive decrees since Algeria's independence until 1998, when the current law No. 98-04 was promulgated. The findings reveal that local actors such as associations and the local population are poorly involved in participation and decision-making. The management of safeguarded areas in Algeria is a government-led process in in which the main actors are the relevant government and its institutions. Received: 13 February 2023 / Accepted: 23 April 2023 / Published: 5 May 2023